The Effect of Problem Based Learning Models with Question Cards on Environmental Pollution Materials on Problem Solving Ability, Scientific Attitudes, and Student Learning Outcomes - Elvi Fuspita Dila*; Slamet Suyanto (Universitas Syiah Kuala, 2023)
Problem solving ability (PSA) is one of the skills that is the focus of the 21st century, besides that scientific attitudes and learning outcomes are also important components that must be possessed by students. This research aims to determine the effect of problem based learing (PBL) with question cards on environmental pollution on PSA, scientific attitudes, and student learning outcomes. The type of research used a quasi-experimental study using a nonequivalent pretest-posttest control group design. Sampling used a cluster random sampling technique. Data collection used PSA description questions, scientific attitude questionnaires, and multiple-choice test to measure the learning outcomes. Data analysis techniques used descriptive analysis, multivariate analysis of variance (Manova) test, and N-gain test. The average results of students in the experimental class were higher than those in the control class. The multivariate analysis of variance test results obtained a Sig. 0.000, and the N-gain test result in the experimental class obtained moderate criteria. Based on the results it is concluded that the PBL model with question cards have a significant effect